Status and Prospects of Agricultural Growth Domestic Product in the Kingdom of Saudi Arabia - Abda Abdalla Emam; Amal Saeed Abass; Nagat Ahmed Elmulthum; Mutasim Elrasheed (SAGE Open, 2021)
The Kingdom of Saudi Arabia (KSA) has set Vision 2030 to reduce the total dependency of the country oil sectors, diversifying the economy and achieving sustainable food security. This necessitated conducting this study which aimed at estimating and analyzing the association and impact of selected agricultural subsectors (dates, honey, fish, chicken, and cattle) on Agricultural Growth Domestic Product (AGDP) of KSA, and identifying the leading subsector in the economy that might substantially affect AGDP and other subsectors. Unit root test, Johansen co-integration, vector error correction model (VECM), multiple regression techniques, and impulse test were used in analyzing the secondary data that covered the period from 1985 to 2017. Results revealed the presence of long-run co-integration between designated variables. Only the coefficient of adjustment parameter for dates (as dependent variable) is negative (−5.42) and significant (critical t value = −2.52 with p = .02), meaning that the model was able to correct its past-time disequilibrium. Furthermore, short-run causality was noticed between few variables. The regression analysis results indicated the existence of positive and significant relationships between the dependent (AGDP) and each of the independent variables: cattle (0.83; p = .00), honey (50.05; p = .06), and chicken (0.07; p = .00). On the contrary, results of the impulse tests showed that the cattle subsector is leading in the economy. Accordingly, cattle, honey, and chicken subsectors should be given high priority in the government investment policy.